Examination of the Effect of Positive Psychology- based Group Counseling on Lying Tendencies - Muhammet Aykuthan Ulusoy; Osman Sezgin (Spiritual Psychology and Counseling)
This study was carried out to apply positive psychology-based group counseling activities, which were prepared to reduce the tendency of 7th grade students to lie and created considering Turkish-Islamic cultural values, and to test the effectiveness of the activities. In the quantitative part of the study in which the mixed method design was preferred, a quasi-experimental design consisting of experimental, control, and placebo groups was used. The quantitative phase of the study was carried out with 68 students, 22 of whom were in the experimental group, 24 in the control group, and 22 in the placebo group, studying in a secondary school in Gaziantep where permission for the study was obtained. The study group for the quantitative stage of the study was determined by the analogous cluster sampling method. The lying tendency scale and the assertiveness inventory were used as data collection tools for this stage. The study group at the qualitative stage, which was completed by performing a case study, was determined using the criterion sampling method and was carried out with the teachers and parents of the experimental group. In the qualitative part of the study, a structured interview form was used as a data collection tool. The study found a significant difference in the lying of the experimental group, no significant difference in the lying tendency of the control and placebo group, significant differences between the difference scores of the groups’ lying tendencies, and a significant difference in the assertiveness scores of the placebo group.